Analysis of aircraft maintenance related accidents and serious incidents in Nigeria - Habib, Khadijah Abdullahi; Turkoglu, Cengiz (MDPI, 2020)
The maintenance of aircraft presents considerable challenges to the personnel that maintain them. Challenges such as time pressure, system complexity, sparse feedback, cramped workspaces, etc., are being faced by these personnel on a daily basis. Some of these challenges cause aircraft-maintenance-related accidents and serious incidents. However, there is little formal empirical work that describes the influence of aircraft maintenance to aircraft accidents and incidents in Nigeria. This study, therefore, sets out to explore the contributory factors to aircraft-maintenance-related incidents from 2006 to 2019 and accidents from 2009 to 2019 in Nigeria, to achieve a deeper understanding of this safety critical aspect of the aviation industry, create awareness amongst the relevant stakeholders and seek possible mitigating factors. To attain this, a content analysis of accident reports and mandatory occurrence reports, which occurred in Nigeria, was carried out using the Maintenance Factors and Analysis Classification System (MxFACS) and Hieminga’s maintenance incidents taxonomy. An inter-rater concordance value was used to ascertain research accuracy after evaluation of the data output by subject matter experts. The highest occurring maintenance-related incidents and accidents were attributed to “removal/installation”, working practices such as “accumulation of dirt and contamination”, “inspection/testing”, “inadequate oversight from operator and regulator”, “failure to follow procedures” and “incorrect maintenance”. To identify the root cause of these results, maintenance engineers were consulted via a survey to understand the root causes of these contributory factors. The results of the study revealed that the most common maintenance-related accidents and serious incidents in the last decade are “collision with terrain” and “landing gear events’’. The most frequent failures at systems level resulting in accidents are the “engines” and “airframe structure”. The maintenance factors with the highest contribution to these accidents are “operator and regulatory oversight”, “inadequate inspection” and “failure to follow procedures”. The research also highlights that the highest causal and contributory factors to aviation incidents in Nigeria from 2006 to 2019 are “installation/removal issues”, “inspection/testing issues”, “working practices”, “job close up”, “lubrication and servicing”, all of which corresponds to studies by other researchers in other countries
Keywords: Nigerian aviation accidents; aircraft maintenance; airworthiness; aviation accidents; flight safety